A strategy for agricultural Statistics in Ghana - Quiñones, Esteban J.; Muñoz, Juan; Ngeleza, Guyslain K. (International Food Policy Research Institute, 2011)
Agriculture is the backbone of the Ghanaian economy. It plays an important role in the socioeconomic development of Ghana as it contributes to ensuring food security, provides raw materials for local industries, generates foreign exchange, and provides employment and incomes for most of the population (especially those living in the rural areas), thereby contributing to economic development and poverty reduction. The central goal of Ghana's current development strategy, which is detailed in the Poverty Reduction Strategy II (GPRS-II), is to accelerate economic growth in order to achieve middle-income status within a measurable planning period. Subsequently, the government has placed a focus on implementing agricultural policies to bring more land under cultivation in order to generate a rapid supply response that will quickly benefit the poor in rural areas.1 These interventions are also intended to help develop a private agricultural sector that contributes to accelerated and sustained growth in the long run. Monitoring and evaluating the progress of these initiatives requires quality agricultural data for large-scale and household-based production that is collected frequently (in order to address the dynamics of agricultural production) on a spatially disaggregated level. This suggests the need for a system that regularly produces precise agricultural statistics on an annual basis at the district level. This is an important consideration because numerous interventions are currently implemented at that administrative level and many more will be operationalized at the district level in the future as Ghana continues to decentralize. However, recent data gathering activities by the Ghana Statistical Service (GSS) and the Statistics, Research, and Information Directorate (SRID) of the Ministry of Food and Agriculture (MoFA) do not currently meet these requirements. Future agricultural surveys must address this gap in order to support the government's interventions and planning processes and, in turn, maximize the effectiveness of agricultural growth and poverty reduction efforts.